2007
DOI: 10.1111/j.1600-6143.2007.01995.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplant Glomerulopathy: Ultrastructural Abnormalities Occur Early in Longitudinal Analysis of Protocol Biopsies

Abstract: Transplant glomerulopathy (TXG) presents a distinctive pattern of glomerular abnormalities. The aim of this study was to describe its sequential ultrastructural pathology. A paired cohort study of 228 protocol biopsies, from our longitudinal database (n = 1345), compared TXG (7 patients, 95 biopsies) and controls (8 patients, 133 biopsies). Ultrastructural morphometry and C4d immunoperoxidase were evaluated from implantation to 5 years after transplantation against sequential histology and functional changes.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 30 publications
8
118
1
1
Order By: Relevance
“…This finding agrees with recently published studies (25)(26)(27)(28)(29). Wavamunno et al (30) showed that endothelial and subendothelial ultrastructural abnormalities in glomerular and peritubular capillaries are sensitive early markers of CTG. They are associated with C4d deposition subsequently detected by light microscopy.…”
Section: Discussionsupporting
confidence: 82%
“…This finding agrees with recently published studies (25)(26)(27)(28)(29). Wavamunno et al (30) showed that endothelial and subendothelial ultrastructural abnormalities in glomerular and peritubular capillaries are sensitive early markers of CTG. They are associated with C4d deposition subsequently detected by light microscopy.…”
Section: Discussionsupporting
confidence: 82%
“…Remarkably, in the cases previously diagnosed as TCMR or even in those without histologic lesions, the presence of EndMT marker expression was associated with progressive graft dysfunction and increased proteinuria during follow-up, which is compatible with indolent, subhistologic ABMR. 5,[21][22][23] Indeed, the diagnosis of ABMR was found in subsequent biopsies in a majority of those grafts with EndMT marker expression when a second biopsy was performed. In contrast, those with EndMT-negative grafts maintained very stable graft function for up to 4 years after the biopsy and none of those grafts had ABMR in subsequent biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…8 Early, subdiagnostic findings include an "activated" aspect of glomerular endothelial cells (GECs), with accumulation of mitochondria, Golgi apparati, and ribosomes, and a transition from fenestrated to continuous endothelium. 9 Diagnostic findings are double contours of the glomerular basement membrane, visible by light microscopy, involving 10% or more of at least one glomerulus with mesangial proliferation. 2 Similar changes are frequently present in the peritubular capillaries.…”
Section: Transplant Glomerulopathy (Txg) Can Show Secondary Focal Andmentioning
confidence: 99%